The relationship between entrepreneurship education and entrepreneurial competencies among students in Universiti Utara Malaysia - Nurul Nadia, Mohd Nazari (2018)
Even though entrepreneurship education has been offered and recognized widely, there is still issues arise for the students' level of entrepreneurial competencies. The entrepreneurial competencies among graduates f re still questionable and largely unexplained. Therefore, based from a sample size of 118 students of Bachelor of Entrepreneurship (Hons.), Universiti Utara Mala, sia (UUM) Sintok, this research paper is conducted to determine whether the entrepreneurship education dimension that consists of teaching methods, contents of study, infrastructure facilities and resources, and quality of lecturers has an effect on students' entrepreneurial competencies. This study uses correlation and regression analysis to analyse data. Based on the correlation analysis, it was found tihat there is significant correlation between the predictor variables (teaching methods, contents of study, infrastructure facilities and resources, and quality of lecturers) and students' entrepreneurial competencies. For regression analysis, two variables which are teaching methods and infrastructure facilities and resources have significant relationship with students' entrepreneurial competencies. Contradict to prediction, the other two variables which are contents of study and quality of lecturers have insignificant relationship with students' entrepreneurial competencies. The findinks of this study have implication for both theory and practice. The Human Capital T~bory is used and supported in this study. Higher educational institutions and lecturers should provide more comprehensive entrepreneurship education for I the students by improving and maintaining the infrastructure facilities and resources, and apply more creative and innovative teaching methods for entrepreneurship !education in order to enhanced the students' entrepreneurial competencies.